Complete solution of the extended EOQ repair and waste disposal model with switching costs - Nadezhda Kozlovskaya; Nadezhda Pakhomova; Knut Richter (European University Viadrina, Department of Business Administration and Economics, 2015)
The EOQ repair and waste disposal problem was studied first by Richter, 1997. A first shop is providing a homogeneous product used by a second shop at a constant demand rate. The first shop is manufacturing new products and it is also repairing products used by a second shop, which are then regarded as being as good as new. The products are employed by a second shop and collected there according to a repair rate. The other products are immediately disposed of as waste. At the end of some period of time, the collected products are brought back to the first shop and will be stored as long as necessary and then repaired. If the repaired products are finished, the manufacturing process starts to cover the remaining demand for the time interval. The model was extended by Saadany and Jaber, 2008 to the problem of minimizing the total cost of production, remanufacturing and inventory while incorporating additional switching costs. The switching cost is incurred when the process shifts from repair to production and from production to repair. However, in their paper the authors did not provide a complete solution to this complex problem. We provide the solution in this paper.
Keywords: 330; EOQ model; Production/recovery; Reuse; Waste disposal; Switching cost